JONASSONITE FROM THE BELOGORSKOE IRON DEPOSIT (SIKHOTE-ALIN) - E.V. Perevoznikova; V.T. Kazachenko; P.P. Safronov (Минералогия)
The paper describes a rare Au–Bi sulfide (jonassonite) from the Belogorskoe iron deposit (Sikhote-Alin), the ore bodies of which are composed of metalliferous sediments that underwent contact metamorphism (T ~550 °С, Plithostatic ~1.5 kbar) and late hydrothermal processes (T 350–415 and 271 °С or slightly lower). Jonassonite is found in products of hydrothermal alteration of metamorphic bustamiteandradite (with a low amount of Mn-bearing hedenbergite, scheelite, lollingite and baryte) rocks composed of calcite, fluorite, native bismuth, bismuthinite, joseite A, an unnamed AgBiS2 phase, cosalite, Mo-bearing scheelite, povellite-molybdenite and other minerals. Jonassonite is intergrown with anhedral calcite aggregates in andradite and forms grains with sections (~5 × 7 µm) close to ellipsoid shape. The mineral contains up to 2.29 wt. % Te, which most likely isomorphically substitutes S. Jonassonite formed at a temperature not exceeding 271 °C during hydrothermal alteration of metamorphic mineral assemblages.